2018
DOI: 10.1140/epjc/s10052-018-6293-z
|View full text |Cite
|
Sign up to set email alerts
|

Cosmological consequences in the framework of generalized Rastall theory of gravity

Abstract: The paper deals with generalized Rastall theory of gravity and its cosmological consequences in the background of homogeneous and isotropic flat FLRW model with perfect fluid as the matter context. The model shows a non singular era (emergent scenario) at the early phase of expansion for a particular choice of the Rastall parameter. Also the model finds to be equivalent to the particle creation mechanism in Einstein gravity in the framework of non-equilibrium thermodynamics. Universal thermodynamics is briefly… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 49 publications
1
50
0
Order By: Relevance
“…In this case d 0 is a free parameter, and some outcomes of this proposal in various cosmic eras have also been studied in Ref. [62]. Accepting this proposal along with considering the unit κ = 8πG 0 and also assuming G(H 0 ) = G 0 (which helps us in finding d 0 ), one easily reaches…”
Section: A Another Possibilitymentioning
confidence: 96%
See 2 more Smart Citations
“…In this case d 0 is a free parameter, and some outcomes of this proposal in various cosmic eras have also been studied in Ref. [62]. Accepting this proposal along with considering the unit κ = 8πG 0 and also assuming G(H 0 ) = G 0 (which helps us in finding d 0 ), one easily reaches…”
Section: A Another Possibilitymentioning
confidence: 96%
“…In Ref. [62], choosing λ = (1 + d 0 H)/[3κ(w + 1)], in which w ≡ p/ρ (where p and ρ denote the pressure and energy density of the cosmic fluid, respectively), it has been shown that non-singular cosmic evolution is obtainable in GRT. In this case d 0 is a free parameter, and some outcomes of this proposal in various cosmic eras have also been studied in Ref.…”
Section: A Another Possibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Rastall's gravity has extensively been studied in different cosmological contexts. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. A qualitative study of Rastall gravity by using phase plane analysis may give insight on class of solutions available in this theory.…”
Section: Introductionmentioning
confidence: 99%
“…The exploration of thermodynamic properties at apparent horizon in Rastall gravity with entropy correction have been done by Bamba et al [19]. Das et al [20] have discussed cosmological consequences and universal thermodynamics in Rastall gravity by illustrating a complete cosmological history starting from inflation to late-time acceleration. Cruz et al [23] have presented a thermodynamic discussion of Rastall gravity by introducing chemical potential.…”
Section: Introductionmentioning
confidence: 99%